"Queering" African American religious history. Issue 7 (7th June 2019) - Greene‐Hayes, Ahmad
Abstract: This article raises questions about how scholars of African American religions and of Black Queer Studies have historically and historiographically rendered queer and transgender persons as being devoid of a religion of their choosing. It calls for research on LGBTQ+ persons in African American religious history and discusses the necessity of "queering" theories and methods in the study of African American religions. To do this, it traces a genealogy of historians of African American religious history "queering" the study of African American religions in order to analyze the state of the field and chart new directions for future study.